WATER FOR COMMERCIAL OIL SHALE DEVELOPMENT IN UTAH: ALLOCATING SCARCE RESOURCES AND THE SEARCH FOR NEW SOURCES OF SUPPLY (Utah Environmental Law Review; Vol 30 No 1 (2010), 2010)
72 1024x768 Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} While oil shale development could provide significant energy resources, a commercial oil shale industry has thus far failed to develop. In fact, oil shale has long been held forth as a promising answer to U.S. national energy needs only to fall victim to repeated boom-bust cycles, most recently in the 1970s and early 1980s. Today, concerns over adverse environmental impacts, fluctuations in the price of oil, and regulatory uncertainty are often cited as obstacles to the development of oil share as a viable source of energy. These concerns, combined with today's challenging economic climate, complicate efforts to obtain up-front funding for oil shale development. Given oil shale's considerable challenges and lack of prior success, it is not surprising that oil shale opponents highlight the numerous promises that oil shale is the fuel of the future and that these promises have repeatedly failed to materialize. However, for the past three decades, several large energy companies and a number of smaller innovators have been working quietly towards cost-effective and environmentally acceptable means of producing oil from shale. Most of these efforts have been located on non-federal land and the details of ongoing research efforts are often shrouded in secrecy. While the details are murky, technology developers recognize the major constraints to commercial oil shale development and have been working to address these issues. While carbon emissions, land use and surface impacts, impacts to protected species and water quality are all potential showstoppers, great attention has been focused on water use and availability. This latter issue is the focus of this paper and where we now turn.